Penerapan Algoritma Simple Additive Weighting Sistem Pendukung Keputusan Seleksi Penjurusan di SMKN 1 Kota Salatiga - Priyadi, Jonathan Mario Dwi; Suprihadi (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
The admission of new students (PPDB) involves a selection process that must be conducted quickly and accurately for incoming students. SMKN 1 Salatiga anticipates that, during the registration process, participants in the selection may exceed the school-provided quota (capacity). Additionally, SMKN 1 Salatiga has limited expert staff to operate mathematical calculation formulas for optimally determining final decision outcomes. This research employs empirical methods or field research, analyzed using the Simple Additive Weighting (SAW) method. This method aims to expedite the process of determining selection results, enabling faster outcomes for students who pass or fail. The results of this study indicate that the SAW method effectively reduces the screening time for students declared as Passed or Failed during the selection process at SMKN 1 Salatiga.